A Qualitative Study of Stressors in Problem-Based Learning Among First-Year Nursing Students - Aiyub, Aiyub; Risaharti, Risaharti; Novitayani, Sri; Kartinazahri, Kartinazahri; Astuti, Puji (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Background: Problem-based learning actively engages students in real-world problem-solving while developing vital soft skills such as teamwork, communication, and interpersonal collaboration. However, the shift from teacher-centered learning in secondary school to student-centered learning, like PBL in nursing college, can be highly stressful for first-year nursing students as they adapt to this new educational model. Methods: The study employs a qualitative design. Data were gathered from 85 first-year nursing students through a paper-based questionnaire, and analysed using qualitative content analysis. The data were systematically examined to extract codes, categories, and themes aligned with the research objectives. Results: The study identified two major themes: (1) academic stressors—including challenges related to teaching materials, schedules, lecturers, and assignments; and (2) Non-academic stressors—involving social adjustment, financial difficulties, and family-related issues. Conclusion: First-year nursing students encounter both academic and non-academic stressors in problem-based learning, with infrastructural deficiencies and sociocultural barriers emerging as significant factors. Integrating stress and coping frameworks, offers a theoretical lens to examine how educational environments and cultural contexts influence student adaptation. Practically, institutions must improve facilities, establish culturally responsive support systems, and provide structured mentorship to enhance resilience and optimize learning outcomes among novice nursing students.